Decolourisation of Synthetic Dyes by Endophytic Fungal Flora Isolated from Senduduk Plant (Melastoma malabathricum) - Ngui, Sing Ngieng; Azham, Zulkharnain; Hairul Azman, Roslan; Ahmad, Husaini (Hindawi Publishing Corporation, 2013)
Atotal of twenty endophytic fungi successfully isolated fromMelastomamalabathricum(Senduduk) were examined for their ability to decolourise azo dyes: Congo red, Orange G, andMethyl red and an anthraquinone dye, Remazol Brilliant Blue R. Initial screening on the glucose minimal media agar plates amended with 200mg L−1 of each respective dye showed that only isolate MS8 was able to decolourise all of the four dyes. The isolate decolourised completely both the RBBR and Orange G in the agar medium within 8 days. Further quantitative analysis of the dye decolourisation by isolate MS8 in aqueous minimal medium showed that isolate MS8 was able to decolourise all the tested dyes at varying levels. Dye decolourisation by the isolate MS8 was determined to be 97% for RBBR, 33% for Orange G, 48% for Congo red, and 56% for Methyl red, respectively, within a period of 16 days. Molecular identification of the fungal isolate MS8 using primer ITS1 and ITS4 showed that isolate MS8 shared 99% sequence similarity with Marasmius cladophyllus, a Basidiomycete. The ability to decolourise different types of dyes by isolateMS8 thus suggested a possible application of this fungus in the decolourisation of dyestuff effluents.